ภาวะเครียดของผู้ปกครองเด็กพิการที่นำบุตรมารับบริการที่ศูนย์ การศึกษาพิเศษ ส่วนกลาง กรุงเทพมหานคร - พิมพ์นารา จงไพศาลสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this cross-sectional descriptive study was to explore the stress and associated factors of parents with disable children that attended at Special Education Center Central Region, Bangkok. Population studied were 118 parents with disable children. The research instruments were Demographic Questionnaire, Social Support Questionnaire, and Parent Stress Test. The relationship between the parents’ stress level and associated factors were analyzed by using chi-square test. Logistic regression was used to identify the predictors of stress in parents with disable children. A p-value of less than 0.05 was considered statistically significant. The results showed that most of parents with disable children that attended at Special Education Center were female(88.1%) with average age of 40.7 ± 8.9 years. About half of the parents (52.6%) had the high-to-highest level of stress and the mean score of parents’ stress was 3.5 (SD=0.6). The associated factors of parents’ stress included parents’ financial status (p<0.01), parents’ educational level, parents’ occupation, parents’ perceiving toward severity of disable children, and social supporting (p<0.05). After performing logistic regression, the remaining predictors of high-to-highest level of stress were parents’ educational level (p <0.01), parents’ occupation, parents’ financial status and parents’ perceiving toward severity of disable children (P <0.05). The result of this study will be information for the relevant official to plan and encourage parents with disable children to aware and manage their stress appropriately that might be beneficial for good mental health and affect on the efficient nurture.